OBSTACLES IN LEARNING TRANSLATION (A Study at the Sixth Semester Students of English Department of FKIP UKI Toraja) - Viktor Siumarlata; Yunita Pamarruan; Yizrel Nani Sallata (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2018)
The objective of the research was to find out the obstacles in learning translation by the sixth semester students of English Department of FKIP UKI Toraja.  In this research, the researcher used qualitative method. The population of this research was the sixth semester students English Department of FKIP UKI Toraja. To collect the data, the researcher used interview at campus and. The researcher used accidental sampling and there were 10 students as respondents. Then the data were analyzed by using the theory of Miles and Huberman (2007). Based on the result above, the researcher found that there were many of obstacles faced by the students in learning translation, namely there are no intention and will, lack of confidence, make things easy, not knowing the benefits of learning translation, has no learning purpose, easy to forget something and lack of grammar.